Self-tuned programmable active-R square wave generator - Al-Ali, A.R. (1994)
Self-tuning of a digitally programmable active-R square wave generator is investigated. A single-chip-mode microprocessor is used as a microcontroller. The microcontroller continuously monitors and automatically corrects the shift in the output frequency that may be caused by temperature drift, component mismatch, aging, and/or any other environmental changes